Pemanfaatan Artificial Intelligence untuk Peningkatan Literasi Digital pada Pengajaran di Lingkungan Perbatasan - Muhammad, Muhammad; Dzulqarnain, Muhammad Faqih; Abdul Fadlil; Sutikno, Tole (CORISINDO 2025, 2025)
The utilization of technology, particularly Artificial Intelligence (AI), in education is crucial, especially in border regions that often face challenges related to digital literacy. This study aims to explore and implement AI technology to enhance digital literacy in teaching within border environments. The method used is community service involving training on the use of AI to support the learning process in several schools in border areas. In this activity, AI applications such as text-to-speech, automatic answer analysis, and providing improvement recommendations are used to assist students with special needs and enhance the effectiveness of learning evaluations. Survey results conducted with 40 respondents show that 100% agree that AI can help analyze student answers and provide improvement recommendations. Furthermore, 87.5% of participants stated that the digitalization of traditional knowledge through AI can help preserve local culture for future generations. Additionally, 50% of respondents agreed that the use of AI technologies, such as text-to-speech, can improve inclusivity in education, particularly for students with special needs. The survey results indicate that AI improves accessibility to education and supports more effective learning management in areas with limited technology access. This community service demonstrates that the application of AI has the potential to improve the quality of education in border regions, while also promoting the preservation of local culture and inclusivity within the education system.